Relating open-circuit voltage losses to the active layer morphology and contact selectivity in organic solar cells. Issue 26 (18th June 2018) - Tang, Zheng; Wang, Jing; Melianas, Armantas; Wu, Yang; Kroon, Renee; Li, Weiwei; Ma, Wei; Andersson, Mats R.; Ma, Zaifei; Cai, Wanzhu; Tress, Wolfgang; Inganäs, Olle
Abstract : By manipulating the active-layer morphologies in OSCs, we achieve different open-circuit-voltages without affecting the energy of charge-transfer state. Abstract : We demonstrate that voltage losses due to both radiative and non-radiative recombination of charge carriers are strongly dependent on D/A phase separation. By processing the active layer with various solvent additives, we create distinct morphologies that lead to significantly different device open-circuit voltages ( V OC ), even though the charge transfer state energy ( E CT ) of the D/A blend remains rather constant. We find that radiative recombination losses are significantly increased for a finely intermixed morphology, due to the large D/A interface area. This leads to a total recombination loss of E CT − qV OC ≈ 0.7 eV. However, considerably smaller losses (0.5 eV), due to suppressed non-radiative recombination, are possible in solar cells where the D/A materials are organized to only allow for selective charge carrier extraction. Using a drift diffusion model, we show that the origin of the reduced non-radiative recombination losses is related to an effect which has not been considered for 'optimized' solar cells – the suppression of minority carrier diffusion to the 'wrong' contact. Our results suggest that the built-in field is not sufficiently strong even in 'optimized' organic solar cells and that selective carrier extraction is critical for further improvements in V OC .